2012
DOI: 10.1088/0741-3335/54/2/025001
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the edge current evolution and comparison with neoclassical calculations during MAST H-modes using motional Stark effect

Abstract: Edge Localized Modes (ELMs), that are present in most tokamak H-(high confinement) modes, can cause significant damage to plasma facing components in fusion reactors. Controlling ELMs is considered necessary and hence it is vital to understand the underlying physics. The stability of ELMs is typically expressed in terms of the pressure gradient ∇p in the edge and the edge current density j φ . Both ∇p and j φ are usually derived from profiles fitted to the measured edge density and temperature profiles, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…The edge pressure gradient has been well diagnosed in many ELM mitigation scenarios, but measurements of the edge current density have only recently become available. The measurements from DIII-D [21], MAST [22], and ASDEX-Upgrade [23] have all shown that the pre-ELM current density in the pedestal is consistent with a neoclassical nature, i.e. it is driven by gradients in the temperature and density profiles.…”
Section: Introductionmentioning
confidence: 93%
“…The edge pressure gradient has been well diagnosed in many ELM mitigation scenarios, but measurements of the edge current density have only recently become available. The measurements from DIII-D [21], MAST [22], and ASDEX-Upgrade [23] have all shown that the pre-ELM current density in the pedestal is consistent with a neoclassical nature, i.e. it is driven by gradients in the temperature and density profiles.…”
Section: Introductionmentioning
confidence: 93%
“…The aim of this paper is to show the effect of applying non-axisymmetric fields to tokamak plasmas. The pressure and safety factor profiles used here are shown in which includes constraining the reconstructed equilibrium with magnetics, Thomson Scattering, motional Stark effect and D α light at the boundary [22], for a lower single null (LSND) plasma. The plasma boundary for this equilibrium is shown in Figure 3.…”
Section: Axisymmetric Equilibriummentioning
confidence: 99%
“…The pressure and safety factor profiles used here are shown in Figures 1 and 2. They are realistic profiles typical of an axisymmetric reconstruction using EFIT, which includes constraining the reconstructed equilibrium with magnetics, Thomson Scattering, motional Stark effect and D α light at the boundary [22], for a lower single null (LSND) plasma. The plasma boundary for this equilibrium is shown in Figure 3.…”
Section: Axisymmetric Equilibriummentioning
confidence: 99%
“…Direct measurements of the edge current density in a tokamak can be achieved by using a Motional Stark Effect (MSE) diagnostic, such as at MAST [7]. A second option is to measure the Zeeman splitting of lithium 2s-2p transition lines, such as at DIII-D [8].…”
Section: Introductionmentioning
confidence: 99%